Mathematics Learning Model in Elementary School to Developing Critical Thinking - Indrawati, Delia (International Conference on Elementary Education, 2022)
21st-century learning is about material and critical thinking skills, collaboration, communication, creativity, and character. During the learning tools workshop, researchers as instructors found a tendency for teachers participating in Teacher Professional Education (PPG Daljab) to be confused about the learning model. The result is that most teachers use models of problem-based learning and project-based learning. If there is no other choice, there may be a lack of literacy regarding learning models to develop students' critical thinking. This study aims to reveal the nature of critical thinking learning and alternative learning models in developing students' critical thinking. The method used in this study is a literature review of articles on Google Scholar. The literature review results include the nature of critical thinking learning to facilitate students with constructing thinking, adapting, evaluating, and planning a follow-up. Alternative learning models include problem-based learning, problem posing, project-based learning, reciprocal teaching, scientific, discovery learning, inquiry, discovery, cooperative learning, ethnomathematics, steam, and realistic mathematics approach (RME). This article is expected to provide convenience for elementary school teachers in choosing various learning models to develop students' critical thinking.